Christians and public life in colonial South India, 1863-1937 : contending with marginality - Mallampalli, Chandra, 1965- (RoutledgeCurzon, 2004)
"This book tells the story of how Catholic and Protestant Indians have attempted to find their place within the evolving Indian nation. Ironically, British rule in India did not privilege Christians, but pushed them to the margins of a predominantly Hindu society. Drawing upon wide-ranging sources, the book first explains how the Indian judiciary's "official knowledge" isolated Christians from Indian notions of family, caste and nation. It then describes how different varieties and classes of Christians adopted, resisted and reshaped both imperial and nationalist perceptions of their identity. Within a climate of rising communal tension in India, this study finds immediate relevance."--Jacket